Exploring effective interventions to reduce Self-Harm behavior in Adolescents: A scoping review - Kurniawan Kurniawan; Andis Pratama; Asna Amalia; Aulia Nida Robbani; Artanti Lathifah; Khoirunnisa Khoirunnisa; Aep Maulid Mulyana (Elsevier, 2024)
Background: Self-harm behavior can occur repeatedly in a person and often occurs and develops in adolescence, which can have a negative impact. Interventions are needed to assist in preventing and reducing self-harm behavior, especially in adolescents. Purpose: This study aimed to explore interventions that can be used to help reduce self-harming behavior in adolescents. Methods: This study used a scoping review and PRISMA-ScR. The databases used include Pubmed, CINAHL, Scopus, and Garuda. The keywords used Boolean operators and consisted of English and Indonesian keywords. Both English and Indonesian keywords included Adolescent AND Intervention AND Self-harm. The inclusion criteria included articles published in 2018-2023, Randomized Controlled Trial (RCT) design or Quasi-experimental, and full-text. Studies were excluded if they were not in English and Indonesian. Results: We found seven articles showing that the intervention models for reducing self-harm behavior in adolescents included Acceptance and Commitment Therapy − DEA (ACT-DEA), Mobile Peer Support App, Post-discharge SMS, Functional Imagery Training (FIT), Cutting Down Program (CDP) and Treatment As Usual (TAU), Expressive Writing Therapy, Mind and Body (MAB). Conclusion: Our findings highlight that these interventions are given to control self-harm behavior, express self-emotions to be positive, and provide strategies, advice, and motivation. These findings were expected to be taken into consideration by health workers such as nurses to implement these available interventions as an effort to prevent and reduce self-harm behavior in adolescents. Therefore, this study can also become a reference for further research-related interventions and strategies for self-harm among various populations.